PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMUNIKASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN RUMAH MAKAN SINDANGRERET CABANG SURAPATI BANDUNG - Sary Muthia, - (2017)
Setiap organisasi dituntut untuk selalu dapat menjaga karyawannya agar dapat menampilkan kinerja yang baik dan memelihara karyawannya agar terciptanya suatu tujuan perusahaan.Organisasi akan mampu untuk dikembangkan dan berjalan efektif apabila memahami pentingnya kepuasan kerja karyawannya. Dengan terciptanya kepuasan kerja karyawan, dapat membantu menciptakan tujuan perusahaan dengan baik. Rendahnya tingkat kepuasan kerja karyawan akan menghasilkan kinerja dibawah standard diantara karyawan lainnya, seperti yang dialami oleh Perusahaan Industri Rumah ]=Makan SindangreretcabangSurapati Bandung. Situasi ini membuat Rumah Makan Sindangreret cabang Surapati Bandung menciptakan suatu strategi untuk meningkatkan kepuasan kerja karyawan dalam perusahaan dengan upaya meningkatkan karakteristik pekerjaan dan komunikasi kerja karyawannya. Penelitian inibertujuanuntukmemperoleh (1) gambarankarakteristikpekerjaan, komunikasi kerja dan kepuasan kerja (2)pengaruhkarakteristikpekerjaanterhadapkepuasankerja (3)pengaruhkomunikasikerjaterhadapkepuasankerja. Metode yang digunakanadalahexplanatory surveydengantekhniksampelyaituprobability samplingberjumlah 72 orang.Teknikanalisa data yang digunakanadalahregresi linier bergandadenganalat bantu software computerStatistical Product for Service Solutions (SPPS) 22.0 for windows. Hasiltemuandalampenelitianinimenunjukkanbahwagambarankarateristikpekerjaandalamkategorisesuai,gambarankomunikasikerjadalamkategori efektif,kepuasankerjadalamkategoritinggi, kepuasankerjadipengaruhiolehkarakteristikpekerjaan, kepuasan kerja dipengaruhi oleh komunikasikerja.Berdasarkanhasilpenelitianini, disarankankarakteristikpekerjaan di industri rumah makan dapatmeningkatkan keterampilanyang sesuai dengan kemampuan karyawannya dalamsuatuorganisasi.Dalamsegikomunikasikerjadisarankandapatmeningkatkanhubungan yang baikantarapimpinandanbawahan agar tercapainyatujuanorganisasi.Sehinggadiharapkankarakteristikpekerjaandankomunikasikerjaperludiperhatikanlebihlanjutolehperusahaandalammenunjangkepuasankerjakaryawan.------Every organization is required to always keep employees to be able to show good performance and maintain employees for the creation of a company goal. The organization will be able to be developed and run effectively if it understands the importance of employee job satisfaction. With the creation of employee job satisfaction, can help create the goals of the company well. The low level of employee job satisfaction will result in sub-standard performance among other employees, as experienced by Sindangreret Restaurant Industry Company in Surapati area of Bandung. This situation makes Sindangreret Restaurant in Surapati area branch of Bandung created a strategy to improve employee work satisfaction within the company with efforts to improve job characteristics and employee communication work. This study aims to obtain (1) description of job characteristics, work communication and job satisfaction (2) the influence of job characteristics on job satisfaction (3) the effect of job communication on job satisfaction. The method used is explanatory surveydengan tekhnik sampling that is probability sampling amounted to 72 people. Technique analyze data used is doubled linear regression with software tools computerStatistical Product for Service Solutions (SPPS) 22.0 for windows. The findings of this study indicate that the description of job characteristics in the categorized, the picture of working communication in the category of effective, job satisfaction in high category, job satisfaction influenced by job characteristics, job satisfaction influenced by work communication and job satisfaction influenced by job characteristics and work communication. Based on the results of this study, it is suggested that the characteristics of work in the restaurant industry can improve the skills in accordance with the ability of its employees in an organization. In terms of working communication is suggested to improve the good relationship between the leadership and subordinates in order to achieve organizational goals. So it is expected job characteristics and work communication needs to be considered further by the company in supporting employee job satisfaction.